Confidence and career choices: an experiment - Kai Barron; Christina Gravert (The Scandinavian Journal of Economics, 2022)
Confidence is often seen as an important determinant of success. However, empirical evidence regarding the causal effect of confidence on choices is sparse. Using a stylized laboratory experiment, we examine the effect of an increase in confidence on two important labor market choices: (i) the amount of ability-contingent earnings risk to take on, and (ii) the subsequent effort choice. We find that increased confidence leads subjects to take on more ability-contingent earnings risk. However, effort levels are unaffected. Overall, the upward shift in confidence is detrimental for low-ability workers as a result of high baseline levels of confidence.
Keywords: 300; Beliefs; career choices; experiment; overconfidence; real effort